MENTORING AS A TOOL FOR CAREER AND HUMAN RESOURCE DEVELOPMENT: THE CASE OF THE UNIVERSITY FOR DEVELOPMENT STUDIES - Agalga, J; Thompson, E. S. (UDS International Journal of Development, 2016)
Many organizations including the University for Development Studies (UDS) in Ghana emphasize mentoring programmes through their training and development efforts in order to enhance employee knowledge, skills and ability. The UDS is the only public University in Ghana that was established without being affiliated to an existing university. This situation greatly disadvantaged the institution in terms of its human resource capacity. The aim of this study was to investigate how mentoring might be strengthened to facilitate and augment the University’s quest for qualified human resource. The descriptive survey making use of a questionnaire and key informant interview were used to collect data. Findings of the study revealed that informal mentoring is prevalent on all campuses of the University. It was also found that paucity of mentors, laxity of young employees to avail themselves for mentoring and disrespect are the major challenges impeding mentoring in the institution. The study concludes that formal mentoring should be strengthened to complement the informal mentoring which is already prevalent.